Angular analysis and differential branching fraction of the decay B0s → ϕμ+μ- - Aaij, Roel; Adeva, B.; Adinolfi, M.; Aquines Gutiérrez, Osvaldo; D'Argent, Philippe; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; et al. (Journal of high energy physics, 2015)
An angular analysis and a measurement of the differential branching fraction of the decay Bs0 → ϕμ+μ− are presented, using data corresponding to an integrated luminosity of 3.0 fb−1 of pp collisions recorded by the LHCb experiment at √s=7 and 8 TeV. Measurements are reported as a function of q2, the square of the dimuon invariant mass and results of the angular analysis are found to be consistent with the Standard Model. In the range 1 < q2 < 6 GeV2/c4, where precise theoretical calculations are available, the differential branching fraction is found to be more than 3σ below the Standard Model predictions.